2003
DOI: 10.1111/j.1365-2222.2003.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sublingual immunotherapy on seasonal asthma and skin reactivity in children allergic to Parietaria pollen treated with inhaled fluticasone propionate

Abstract: SummaryBackground Immunotherapy is a recognized treatment for allergic respiratory diseases. Objective To study the usefulness of immunotherapy in combination with optimal pharmacological therapy. Methods Thirty-eight children (8-14 years) suffering from seasonal asthma7rhinoconjunctivitis due to Parietaria poorly controlled by anti-allergic drugs treatment were selected. After randomization according to a double-blind placebo-controlled design they received active sublingual immunotherapy (15 children) or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 20 publications
1
80
0
1
Order By: Relevance
“…Wilson et al (1698) published a Cochrane Collaboration meta-analysis of SLIT in rhinitis and proposed that it was safe and effective. The Cochrane meta-analysis (1699) was followed by several studies which accorded with the results of the review (1103,(1700)(1701)(1702)(1703)(1704)(1705)(1706)(1707)(1708)(1709)(1710)(1711). Moreover, pivotal trials have been carried out and the results on over 600 patients showed convincingly that in grass pollen allergy, SLIT is safe and effective using tablets (1103,1712).…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…Wilson et al (1698) published a Cochrane Collaboration meta-analysis of SLIT in rhinitis and proposed that it was safe and effective. The Cochrane meta-analysis (1699) was followed by several studies which accorded with the results of the review (1103,(1700)(1701)(1702)(1703)(1704)(1705)(1706)(1707)(1708)(1709)(1710)(1711). Moreover, pivotal trials have been carried out and the results on over 600 patients showed convincingly that in grass pollen allergy, SLIT is safe and effective using tablets (1103,1712).…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…25,[34][35][36][37] Two placebocontrolled trials of olive and tree mix allergens with medium risk of bias that enrolled 70 and 98 children, respectively, demonstrated moderate to strong magnitude of effect for SLIT. 36,37 One study of dust mite immunotherapy in 58 children, with a low risk of bias and weak magnitude of effect, showed little improvement with SLIT compared with placebo.…”
Section: Conjunctivitismentioning
confidence: 99%
“…[25][26][27][28][29][32][33][34][35][36][37][38] One-half of the studies evaluated dust mite allergens. 25,26,[32][33][34]38 Risk of bias was low in 4 studies, 27,29,32,34 medium in 6 studies, 26,33,[35][36][37][38] and high in 2 studies. 25,28 Five studies demonstrated significant improvement in rhinitis/ rhinoconjunctivitis scores with SLIT, compared with placebo, with moderate to strong magnitudes of effect.…”
Section: Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…For an individual allergic to particular pollen, the prediction of the start of that pollen's season can allow them to adjust their daily activities so as to avoid contact with the allergen (Peternel et al 2004), or to begin taking medication. Pollen count data is also important for research into allergic rhinitis, in particular for clinical trials into immunotherapy, vaccines and antihistamines, which rely on pollen counts to assess the efficacy of the drugs in relation to the severity of the allergenic stimulus (Keskin et al 2006;Pajno et al 2003;Mirone et al 2004). …”
Section: Introductionmentioning
confidence: 99%